2020
DOI: 10.1016/j.compag.2020.105285
|View full text |Cite
|
Sign up to set email alerts
|

Development of a recurrent neural networks-based calving prediction model using activity and behavioral data

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The Adsorbing Markov Chain Model successfully reduced the interval between calving prediction and calving event to 3 h in 25 Holstein and Brown Swiss cows. Another study reported an accurate prediction of the day of calving but not the exact hour [93]. Generally, authors agree that algorithms correctly classify data on eating, ruminating, lying and standing, but they should be refined before extensive application for precision calving prediction.…”
Section: Performance Of Automatic Sensors and Machine-learning For Re...mentioning
confidence: 99%
“…The Adsorbing Markov Chain Model successfully reduced the interval between calving prediction and calving event to 3 h in 25 Holstein and Brown Swiss cows. Another study reported an accurate prediction of the day of calving but not the exact hour [93]. Generally, authors agree that algorithms correctly classify data on eating, ruminating, lying and standing, but they should be refined before extensive application for precision calving prediction.…”
Section: Performance Of Automatic Sensors and Machine-learning For Re...mentioning
confidence: 99%
“…Recently, machine learning has been actively used in several fields with the development of computer performance. Machine learning in the livestock field is also actively used to analyze animal behavioral pattern [19,20,[26][27][28], to analyze behavior prior to calving [29][30][31], to analyze the voice of livestock [32], and to predict dependent…”
Section: Recurrent Neural Networkmentioning
confidence: 99%
“…Recently, machine learning has been actively used in several fields with the development of computer performance. Machine learning in the livestock field is also actively used to analyze animal behavioral pattern [19,20,[26][27][28], to analyze behavior prior to calving [29][30][31], to analyze the voice of livestock [32], and to predict dependent variables according to various environmental variables [18]. Among several machine learning techniques, ANN has been actively used as a method to accurately predict the dependent variables from independent variables.…”
Section: Recurrent Neural Networkmentioning
confidence: 99%
“…While RusBoosted Tree classifier allows to predict the remaining 8h before calving. The results they have gotten are respectively for BiLSTM and RusBoosted Tree classifier, with an accuracy of 83.34% and 84.16%, a sensibility of 81.9% and of 80.51%, and finally a specificity of 98.72% and 85.74% [29]. Other researchers like Shahriar et al have used 3D-accelerometer sampled at 10Hz and attached to a collar to detect the heat from high activity index derived from time series by means of kmeans algorithm.…”
Section: Cowsmentioning
confidence: 99%